Antioxidant administration on the incidence of preterm premature rupture of membranes: a literature review - Winata, I Gde Sastra; Mahendrata, Prayascita; Wiraputri, Anak Agung Ratih Kusumadewi; Anwar, Meirisa Afifah Nurmalia; Jessica Nathalia (Indonesian Journal of Perinatology, 2025)
One of the obstetric issues that can lead to consequences for both the mother and the unborn child is premature rupture of membranes (PROM).  In Indonesia, 35% of pregnancies ended in preterm rupture of the membranes in 2013.  The incidence of preterm pregnancy is 2% of all pregnancies, while the incidence of term pregnancy ranges from 6 to 19%.  At 37 weeks gestation, the phrase "premature rupture of membranes" is used.  Preterm premature rupture of membranes (PPROM) is the term used to describe when the membranes burst before birth in women whose gestational age is less than 37 weeks.  It is believed that the pathophysiology of premature membrane rupture involves reactive oxygen species (ROS).  The result of premature membrane rupture is anticipated to be impacted by antioxidant supplementation.